2023
DOI: 10.22207/jpam.17.4.03
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions between Metallic Nanoparticles and Cytochrome P450, Alanine Aminotransferase, and Aspartate Aminotransferase Enzymes

Hayat A. Al-Btoush

Abstract: The use of metallic nanoparticles (NPs) in various industrial and biomedical fields is increasing exponentially. As a result, research examining the potentially toxic impact of these NPs on human health is also increasing. Cytochrome P450 (P450s) enzymes are important for the endogenous and exogenous molecules metabolism. Inhibition or induction of these enzymes affects xenobiotic detoxification and causes clinically significant drug toxicity or therapeutic failures. Alanine aminotransferase (ALT) and aspartat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Other studies with more complex nanoparticles, such as Mn 3 O 4 , have also revealed liver toxicity, reactive oxygen species (ROS) associated with CYPs, and altered CYP expression profiles [18]. Recent reviews have discussed this topic in some detail [19,20].…”
Section: Metallic Nanoparticles Metal Clusters and Metal Ionsmentioning
confidence: 99%
“…Other studies with more complex nanoparticles, such as Mn 3 O 4 , have also revealed liver toxicity, reactive oxygen species (ROS) associated with CYPs, and altered CYP expression profiles [18]. Recent reviews have discussed this topic in some detail [19,20].…”
Section: Metallic Nanoparticles Metal Clusters and Metal Ionsmentioning
confidence: 99%